2017
DOI: 10.1111/1756-185x.13153
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk of metabolic syndrome in patients with systemic lupus erythematosus: A meta‐analysis

Abstract: The systematic review and meta-analysis demonstrated the prevalence of MetS in patients with SLE was 26% and the patients with SLE were more prone to having MetS than the control population. The analysis was a basic summary of all relevant researches and provided valuable evidence for prevention and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 49 publications
2
17
0
1
Order By: Relevance
“…It has previously been suggested that the risk of MetS in SLE is approximately double that of control populations. 13 The prevalence of MetS in our cohort was 29%, which is in line with the pooled prevalence of 26% reported in a recent meta-analysis of multinational SLE patients. 13 The prevalence of MetS in SLE has geographical variation, with patients from Europe and Asia having lower prevalence when compared with Africa and South America.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…It has previously been suggested that the risk of MetS in SLE is approximately double that of control populations. 13 The prevalence of MetS in our cohort was 29%, which is in line with the pooled prevalence of 26% reported in a recent meta-analysis of multinational SLE patients. 13 The prevalence of MetS in SLE has geographical variation, with patients from Europe and Asia having lower prevalence when compared with Africa and South America.…”
Section: Discussionsupporting
confidence: 92%
“…13 The prevalence of MetS in our cohort was 29%, which is in line with the pooled prevalence of 26% reported in a recent meta-analysis of multinational SLE patients. 13 The prevalence of MetS in SLE has geographical variation, with patients from Europe and Asia having lower prevalence when compared with Africa and South America. 13 This is considered to be associated with a combination of genetic predisposition along with environmental and lifestyle factors, such as diet.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…SLE patients present a higher risk for developing MetS than healthy controls (HCs). 58,59 A multivariate analysis has associated MetS with disease activity and steroid exposure in a cohort of SLE patients. 60 Since MetS increases the risk of cardiovascular events in the general population, 61 it is also likely that SLE patients with MetS are also at higher risk for cardiovascular disease.…”
Section: Lupus and Sys Temi C Me Tabolis Mmentioning
confidence: 99%